2021
DOI: 10.1055/s-0041-1732365
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Conditions Including Obesity, Diabetes, and Polycystic Ovary Syndrome: Implications for Breastfeeding and Breastmilk Composition

Abstract: Breastfeeding is internationally recognized as the recommended standard for infant nutrition, informed by evidence of its multiple benefits for both mother and baby. In the context of common metabolic conditions such as polycystic ovary syndrome, diabetes (type 1, type 2, and gestational), and obesity, breastfeeding may be particularly beneficial for both mother and infant. However, there is evidence of delayed lactogenesis and reduced breastfeeding rates and duration in women with these conditions, and the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 164 publications
0
10
0
Order By: Relevance
“…23 Studies also showed delayed onset of full breast milk supply for individuals with diabetes. 12,[24][25][26] This presents a concern given the fact that approximately 27% of infants that are born to mothers with diabetes experience hypoglycemic episodes in the immediate postnatal period, and could require formula supplementation or NICU or SCN admission. 27 Early breastfeeding initiation and colostrum expression with ABE can help to stabilize the infant's blood glucose levels more effectively than formula milk and promote breastfeeding exclusivity and possibly even reduce NICU or SCN admission.…”
Section: Discussionmentioning
confidence: 99%
“…23 Studies also showed delayed onset of full breast milk supply for individuals with diabetes. 12,[24][25][26] This presents a concern given the fact that approximately 27% of infants that are born to mothers with diabetes experience hypoglycemic episodes in the immediate postnatal period, and could require formula supplementation or NICU or SCN admission. 27 Early breastfeeding initiation and colostrum expression with ABE can help to stabilize the infant's blood glucose levels more effectively than formula milk and promote breastfeeding exclusivity and possibly even reduce NICU or SCN admission.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, endocrine, cardiovascular, and gastrointestinal conditions were associated with the low milk production cluster. Endocrine conditions are an established risk factor for impaired lactation [ 51 ], through mechanisms related to insulin resistance, breast hypoplasia, and reduced prolactin responsiveness [ 52 ]. Previous studies have found that low milk supply was associated with diabetes in pregnancy [ 53 ], and that fewer women with polycystic ovary syndrome (PCOS) breastfed to 6 months relative to women without PCOS (44.3% vs. 54.2%, respectively) [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Relevant medical history includes any conditions associated with insulin deficiency including gestational or pregestational diabetes, polycystic ovarian disease, anovulatory infertility, and metabolic syndrome. There is an increasing body of evidence suggesting an important role of insulin in lactogenesis and association between insulin resistance and impaired lactation 29–32. Several studies have investigated the role of metformin either prenatally or postnatal to improve breastfeeding outcomes, however, results remain inconclusive 33,34.…”
Section: Disorders Of Lactogenesismentioning
confidence: 99%
“…There is an increasing body of evidence suggesting an important role of insulin in lactogenesis and association between insulin resistance and impaired lactation. [29][30][31][32] Several studies have investigated the role of metformin either prenatally or postnatal to improve breastfeeding outcomes, however, results remain inconclusive. 33,34 A review of the obstetrical course including experience of breast growth during pregnancy, timing and modality of delivery, and perinatal complications such as hemorrhage and preeclampsia can also reveal clues as to the source of the problem.…”
Section: Delayed and Insufficient Lactogenesismentioning
confidence: 99%